Meningkatkan Kemampuan Berbahasa Anak Usia 5-6 Tahun Melalui Metode Read Alaud Di RA Persis 97 - Nurbaeti, Elmi Siti; Choiriyah , Choiriyah; Anggraeni, Rita Intan (CV. ITTC INDONESIA, 2024)
Elmi Siti Nurbaeti (1862050162). Enhancing Language Skills of Children Aged 5-6 Years Through the Read alaud Method at RA Persis 97 Cikajang Garut. Thesis. Bekasi: Universitas Panca Sakti Bekasi. 2024. his research aims to improve the language skills of children aged 5-6 years through the